Volcanic Eruption Triggers a Rare Meteotsunami in the Indian Ocean - N. Anup; B. Rohith; V. Vijith; L. Rose; P. Sreeraj; A. Sabu; K. S. Krishnamohan; B. L. Sudeepkumar; A. S. Sunil; P. S. Sunil (Geophysical Research Letters)
Abstract This study presents the observation and evaluation of a meteotsunami in the Indian Ocean triggered by the Hunga‐Tonga volcanic eruption. The event was detected through tide gauges and bottom‐pressure recordings across the Indian Ocean, with an amplitude of 10–15 cm, lasting for a few days. A numerical model was used to understand the ocean's response to meteotsunami and evaluate the dynamics behind it. The model results show that the sea‐level oscillations result from the ocean waves generated by a propagating Lamb wave. In addition to interaction with bathymetry, refracted and reflected waves also determine the sea‐level variability. Our analysis shows that bathymetric slope plays a vital role in near‐shore processes. The spectral and spatial characteristics of the meteotsunami were reminiscent of seismic tsunamis. Our research on this rare event elucidates the unresolved issues and eventually leads to designing a blueprint for future observation and modeling of meteotsunamis and seismic tsunamis.